Critical factors in Technology Transfer Office (TTO) process that support successful technology transfer within Research Universities (RUs) - Muhammad Sapah, Roszaimah; Ali, Mass Hareeza; Ibrahim, Rahinah (Asian Scholars Network, 2022)
The purpose of this paper is to analyse potentially significant factors in a series of relevant characteristics of universities’ technology transfer offices (TTOs). Previous studies stated that TTO plays an important role in shaping the direction of technology transfer growth in Research Universities (RUs) and could increase the economic growth. However, the success rate of commercialization in RUs innovations are low when compared to start-ups/spinoffs companies against the Intellectual Properties Rights (IPR) produced. Therefore, there is a need to enhance the role of TTO in RUs to enable successful technology transfer. This study conducts a systematic literature review synthesis to identify role and responsibilities of TTO in the process of commercialization, determine critical factors for enabling successful technology transfer and understanding RUs innovation ecosystem for enhancing successful technology transfer. The results provide evidence that TTO which has appropriate institutional structure with entrepreneurial activities could facilitate development of academic entrepreneurship roles thereby motivating successful RUs technology transfer. These results are expected to improve the successful commercialization rate of universities inventions in consistent with the regional economic growth in Malaysia. Future studies are recommended to include development of a framework for nurturing strategic entrepreneurship within TTO to enhance commercialization of innovation through RUs technology transfer.